2021
DOI: 10.3221/igf-esis.58.20
|View full text |Cite
|
Sign up to set email alerts
|

Bending cyclic behavior and scatter-band analysis of aluminum alloys under beneficial and detrimental conditions through high-cycle fatigue regime

Abstract: This article presents the bending fatigue behavior and the scatter-band analysis of aluminum alloys under beneficial conditions of nano-clay-particles and heat-treating, compared to detrimental conditions of the mechanical stress and the corrosion. Moreover, the sensitivity analysis was also done on the stress level, the pre-corrosion phenomenon, the addition of nano-particles and applying the heat treatment on the high-cycle bending fatigue lifetime of the aluminum-silicon alloy. For this objective, gravity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Azadi and Aroo [22] investigated the fatigue behavior of aluminum alloys in bending. They concluded that defects during the shaking molding process led to increased fatigue-corrosion and fatigue life of aluminum alloy reinforced with heat treatment and nanoparticle process by 114% and 128%, respectively, under high stress levels compared to aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Azadi and Aroo [22] investigated the fatigue behavior of aluminum alloys in bending. They concluded that defects during the shaking molding process led to increased fatigue-corrosion and fatigue life of aluminum alloy reinforced with heat treatment and nanoparticle process by 114% and 128%, respectively, under high stress levels compared to aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nanostructures find application in composite materials, where one or more phases, having a nanometer scale, are embedded in a matrix. In terms of their matrix, nanocomposites are generally classified as [3]: ceramic-matrix [4][5][6][7][8][9][10][11][12], metalmatrix [13][14][15][16][17][18][19][20][21] and polymer-matrix nanocomposites [22][23][24][25][26][27][28]. More recently, research on cement-based materials (including concrete, mortar and cement paste) [29][30][31][32][33][34][35] has been trying to exploit the synergies that nanostructures can provide in terms of both improvement of their performance and acquisition of "smart" functions, making cement-based products become electric/thermal sensors or crack repairing materials [36].…”
Section: Introductionmentioning
confidence: 99%